Healing Mechanisms in Islamic Psychology: An Approach to Trauma and Stress - Farhan, Ahmad Farhan; Khair, Fikri Khair (Cattleya Darmaya Fortuna, 2024)
Character education based on the Qur'an is one of the efforts to shape positive student behavior amidst moral challenges in the modern era. This study aims to analyze the effect of character education based on the Qur'an on the behavior of elementary school students. This study used a quantitative approach with a quasi-experimental design involving 60 fourth grade students at an elementary school in [city/area name]. The experimental group (30 students) received Qur'an-based character learning for 8 weeks, while the control group (30 students) followed conventional learning. Data were collected through behavioral observations and questionnaires measuring aspects of honesty, responsibility, and politeness, then analyzed using an independent t-test. The results showed a significant difference (p <0.05) between student behavior in the experimental and control groups, with an average increase in behavioral scores of 18.5% in the experimental group. These findings indicate that character education based on the Qur'an is effective in improving positive student behavior, especially in terms of honesty and responsibility. This study recommends the implementation of a similar approach in the elementary school curriculum to support the formation of students' Islamic character.